2014
DOI: 10.1111/hrd2.00040
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of novel mutations inBRCA1in Iranian families with breast cancer

Abstract: In Iran and the rest of the world, breast cancer (BC) is the most common malignancy in women. Familial history and age are significant risk factors for the development of this disease in Iran. Most hereditary BCs are associated with inherited mutations in the BRCA1 and BRCA2 genes. Some recent studies demonstrated that BRCA1 mutations are seen in high-risk women with family histories of BC. In this report we investigated all BRCA1 exons from 40 female patients with family histories of BC and one BC twin, and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The incidence rate of breast cancer varies in different geographical regions (2). According to Annual Iranian National Cancer Registration Report 2008-2009, breast cancer among Iranian women, has been registered as the second and first most common cancer, with the incidence rate of 11.31% and 24.86%, respectively (3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence rate of breast cancer varies in different geographical regions (2). According to Annual Iranian National Cancer Registration Report 2008-2009, breast cancer among Iranian women, has been registered as the second and first most common cancer, with the incidence rate of 11.31% and 24.86%, respectively (3).…”
Section: Introductionmentioning
confidence: 99%
“…BRCA1 is located on chromosome 17q, and any mutations or changes in this gene can lead to increased risk of breast and ovarian cancers (2, 3).…”
Section: Introductionmentioning
confidence: 99%
“…For example, BRCA1 c.2286A>T (p.Arg762Ser) is classified as a VUS in ClinVar (Table ). This variant has been previously reported in the literature in individuals of East Asian ancestry and has 14 observations in the Exome Aggregation Consortium database. This literature is referenced in ClinVar, and the absence of evidence of variant pathogenicity likely resulted in its uncertain classification.…”
Section: Resultsmentioning
confidence: 53%
“…Different studies in Iran demonstrated various alterations of BRCA1 and BRCA2 genes. In our previous study we had introduced a novel mutation in Khorasan papulation (accession number BankIt1473921 JN686490) (14). However, due to the sequencing of nine patients in present study, not only we found out submitted mutation, but also, no novel mutations did not determine in BRCA1 gene exons.…”
Section: Discussionmentioning
confidence: 53%